Analysis of variance and functional measurement : a practical guide - Weiss, David J. (Oxford University Press, 2006)
Beginning with the basics, then proceeding to more advanced concepts, and including exercises and discussions of how to present the results, this volume explains ANOVA, a set of statistical techniques for analysing the results of controlled or quasi-controlled experiments. It is useful for students and professionals.